Computationally Efficient Light Field Image Compression using a Multiview HEVC Framework - Ahmad, Waqas (Mid Sweden University, 2021)
This software package describes the Light Field (LF) Coding Framework proposed by Ahmad et al. in published paper, "Computationally efficient light field image compression using a multiview HEVC framework", IEEE Access September 2019. The coding framework reads the input LF image, generates multiview sequences, encodes the generated sequences using MVHEVC encoder and finally produces the decoded Mat files. The Mat files contain decoded LF structure, PSNR information and size (in bytes) of the compressed LF image. The detail information of the proposed coding framework is explained in the user manual which is placed inside the MIUN_LFCF Folder. The continuous development of proposed coding framework can be followed on Github project (link provided under other Homepage).

The dataset was originally published in DiVA and moved to SND in 2024.
Computationally Efficient Light Field Image Compression using a Multiview HEVC Framework
Keywords: information technology; informationsteknik; data systems; informationssystem (tekniska system); Engineering and Technology; Teknik